Pemanfaatan Abu Vulkanik Gunung Merapi Sebagai Filler Pada Campuran Lapis Aus (Ac-Wc) Ditinjau Dari Parameter Marshall - Rafik Awaludin; Prihantono Prihantono; Riyan Arthur (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2017)
The rise of the traffic volume which causes road damage due to heavy load and humidity, there must be an improvement to the quality of the road. This research uses Mount Merapi Volcanic Ash waste as a filler in The WearLayerMixture. The aim of this research is to examine if there is a difference between asphalt concrete that uses Mount Merapi Volcanic Ash as its filler and asphalt concrete that uses cement as its filler in terms of Marshall parameter. This research uses experimental method that examines Marshall parameter on five variations of asphalt level, which are 4%, 5%, 6%, 7% and 8% with 6 (six) samples of specimen on each variation. Marshall method resulting the maximum asphalt level at 6% percentage with it’s stability value which is 964,091 kilograms, flow value 3,1milimeters,Marshall Quotient (MQ) value 312,331 km/mm, Void in Mineral Aggregates (VMA) value 17,976%, Void Filled with Bitumen (VFB) value 69,939%,and Void In the Mix (VIM) value 4,947%. Based on the result of this research, it can be concluded that the Mount Merapi Volcanic Ash can be used as a filler in The Wear Layer Mixture for heavy traffic class with 6% of asphalt level.